Asphalt composition comprising a mixture of isocyanate and plasticizer as performance additive

By adding isocyanate and plasticizers to the asphalt composition to form armosetable reactive composite, the constructionability of the asphalt mixture composition under the high RAP content, the anti -low temperature and the cracking, and the rutuality of the car are better. Physical properties and constructionability.

CN115516001BActive Publication Date: 2025-01-28BASF SE
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202180033820.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-19
Filing Date
2021-06-08
Publication Date
2025-01-28
Estimated Expiration
2041-06-08

AI Technical Summary

Technical Problem

The existing asphalt mixture compositions have problems such as poor construction/compression, insufficient low-temperature crack resistance, limited rutting resistance and fatigue behavior under high RAP content.

Method used

By adding 0.1-8 % of isocyanate and 0.1-8 % per plasticizer in the asphalt composition, such as phthalates, phenyl-alnate, etc., thermosettic response combinations are formed to improve asphalt The colloid structure.

Benefits of technology

It significantly improves the anti -rutuality, fatigue behavior, elasticity and low temperature performance of the asphalt mixture composition, improves construction and compactness, and enhances low temperature and cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003931554040000211
    Figure BDA0003931554040000211
  • Figure BDA0003931554040000241
    Figure BDA0003931554040000241
  • Figure BDA0003931554040000242
    Figure BDA0003931554040000242
Patent Text Reader

Abstract

The present invention relates to an asphalt composition, which comprises 0.1-8% by weight of an isocyanate as a thermosetting reactive compound based on the total weight of the composition and 0.1-8% by weight of a plasticizer based on the total weight of the composition, wherein the plasticizer is selected from phthalates, terephthalates, cyclohexanoates, azelaics, acetates, butyrates, valerates, alkylsulfonates, adipates, benzoates, dibenzoates, citrates, maleates, phosphates, sebacates, sulfonamides, epoxy esters, trimellitates, glycerides, succinates, mineral oils and polymer plasticizers or mixtures thereof, wherein the polymer plasticizer is selected from polymers of adipic acid with 2,2-dimethyl-1,3-propanediol and 1,2-propylene glycol isononyl ester, polymers of adipic acid with 1,2-propylene glycol octyl ester and polymers of adipic acid with 1,2-propylene glycol acetate or mixtures thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention generally relates to an asphalt composition comprising an isocyanate and a plasticizer selected from the group consisting of phthalates, terephthalates, cyclohexanoates, azelates, acetates, butyrates, valerates, alkyl sulfonates, adipates, benzoates, dibenzoates, citrates, maleates, phosphates, sebacates, sulfonamides, epoxy esters, trimellitates, glycerides, succinates, mineral oils and polymeric plasticizers or mixtures thereof, wherein the polymeric plasticizer is selected from the group consisting of polymers of adipic acid with 2,2-dimethyl-1,3-propanediol and 1,2-propylene glycol isononyl ester, polymers of adipic acid with 1,2-propylene glycol octyl ester and polymers of adipic acid with 1,2-propylene glycol acetate or mixtures thereof.

[0002] The present invention also relates to a method for preparing an asphalt composition and to its use in an asphalt mixture composition for pavement applications. The asphalt composition of the present invention shows an increase in the functional temperature range, such as the usable temperature range of the bitumen, increased elasticity and lower deformation potential, improved asphalt workability / compactability of asphalt mixture compositions with high RAP content, excellent rutting resistance and fatigue behavior and improved low temperature performance (high crack resistance due to sufficient elasticity).

[0003] Generally speaking, asphalt is a colloidal material that contains different molecular species, classified as asphaltenes and petroleum greases. Asphalt is viscoelastic and thermoplastic, and its properties change over a range of temperatures from extreme cold to extreme heat. Asphalt softens in hot weather and cracks in extreme cold. At low temperatures, asphalt becomes brittle and easily cracks, while at elevated temperatures, asphalt softens and loses its physical properties.

[0004] Pavements continuously oxidize and age during their performance life, leading to durability issues due to increased rigidity and brittleness and reduced ability to relax stress. In addition, increasing the use of recycled asphalt pavement (RAP) materials to save major resources and reduce CO 2 emissions, which requires improved rheology and restoration of properties of asphalt bases containing a high proportion of base derived from RAP and corresponding asphalt mixture compositions.

[0005] The high content of RAP materials in asphalt mixture compositions brings many challenges. The processing properties of asphalt mixture compositions are poor, because the aged asphalt base resulting from the oxidative aging process shows a high softening point and is therefore more viscous. Therefore, the asphalt mixture compositions require higher processing temperatures. In addition, when a large amount of brittle and rigid RAP materials are used, the resistance to low temperature cracking of the corresponding asphalt mixture compositions is seriously affected. It is very desirable to improve the properties and rheology of the asphalt base and the corresponding asphalt mixture compositions, which contain a high proportion of base materials derived from RAP. Conventional prior art modifiers regenerate aged RAP asphalt (so-called regenerators), i.e., the softening point is reduced, the compaction temperature required for asphalt mixture compositions containing a high RAP proportion is reduced (better workability / compactability), and the resistance to low temperature cracking of asphalt mixture compositions with high RAP contents is improved. However, the high temperature properties of the regenerated RAP asphalt mixture compositions, i.e., the rutting resistance and fatigue behavior are not improved, or are even reduced.

[0006] The addition of thermosetting reactive components such as isocyanates as binders, more generally respectively referred to as modifiers, allows the physical properties of the asphalt to remain more constant over a range of temperatures and / or improves the physical properties over the range of temperatures to which the asphalt is subjected.

[0007] Such bitumens modified by addition of base materials or, respectively, modifiers have been known in the prior art for many years. However, there is still a need for improved bitumens in the bitumen industry. This is partly due to the fact that currently known polymer-modified bitumens have many drawbacks. These include, for example, sensitivity to permanent deformation (rutting), flexural fatigue, moisture, reduced elasticity under low temperature operation.

[0008] WO 01 / 30911A1 discloses an asphalt composition comprising about 1-8% polymeric MDI based on the total weight of the composition, wherein the polymeric MDI has a functionality of at least 2.5. It also relates to a process for preparing the asphalt composition using a reaction time of less than 2 hours. The formation of the product MDI-bitumen is measured by an increase in the product viscosity or more preferably by dynamic mechanical analysis (DMA).

[0009] WO 01 / 30912 A1 discloses an aqueous bitumen emulsion which, in addition to bitumen and water, also contains an emulsifiable polyisocyanate, an aggregate composition containing the emulsion and a method for preparing the composition.

[0010] WO 01 / 30913A1 discloses an asphalt composition comprising about 1-5% of a polymerized MD1-based prepolymer based on the total weight of the composition, wherein the polymerized MD1 has a functionality of at least 2.5. It also relates to a method for preparing the asphalt composition.

[0011] EP 0 537 638 B1 discloses a polymer-modified bitumen composition comprising 0.5-10 parts by weight of a functionalized polyoctenamer, up to 100 parts by weight of bitumen and optionally a crosslinker, characterised in that the polyoctenamer is predominantly trans-polyoctenamer and comprises carboxyl groups as well as groups derived from, for example, maleic acid.

[0012] US 2015 / 0191597A1 discloses an asphalt base composition comprising asphalt and a polymer blend, wherein the polymer blend comprises an oxidized high density polyethylene and another polymer selected from maleated polypropylene, polyethylene homopolymer, high crystallinity polyethylene and combinations thereof. It has been found that adding certain polymer blends to the asphalt base composition broadens the PG range and improves the UTI of the asphalt base composition.

[0013] WO 2018 / 228840A1 discloses the modification of an asphalt base with a thermosetting reactive compound, thereby causing the base components to crosslink and produce a strong elastic polymer network, showing improved physical properties while maintaining low temperature performance.

[0014] Therefore, it is highly desirable to provide an asphalt composition and the related preparation method which avoid all the disadvantages associated with the prior art, such as limited elasticity, low rutting resistance, limited fatigue behavior, limited usable temperature range and poor workability of asphalt mixture compositions with high RAP amounts.

[0015] An object of the present invention is to provide an asphalt composition and an asphalt mixture composition, which show improved physical properties in terms of excellent rutting resistance and fatigue behavior of an asphalt mixture composition with a high RAP content, improved low temperature performance, high crack resistance due to sufficient elasticity, and improved asphalt mixture workability. In addition, corresponding asphalt compositions and asphalt mixture composition preparation methods are provided.

[0016] The different physical properties of the bituminous composition were measured by different tests known in the art and will be described in detail in the experimental part.

[0017] It should be understood that the terms used hereinafter are not intended to be limiting, as the scope of the present invention is limited only by the appended claims. In addition, the following examples used in defining terms should be understood that the definitions of the corresponding terms are not limited to the given examples.

[0018] Bitumen / bituminous base / bituminous composition

[0019] According to the present invention, the terms "bitumen", "bitumen base" and "bitumen composition" are used equivalently. Generally speaking, bitumen is a colloidal material containing different molecular species, which are divided into asphaltenes and petroleum greases.

[0020] The bitumen / bitumen base / bitumen composition can be unmodified or modified. Unmodified bitumen / bitumen base / bitumen composition or also so-called paving grade bitumen (base) can have a penetration grade (=pen grade) of, for example, 50 / 70 or 70 / 100 (penetration is determined according to DIN EN 1426). The modified bitumen composition can be, for example, a polymer-modified bitumen (PmB). The corresponding polymer can be selected from thermoplastic elastomers, latex, thermoplastic polymers, thermosetting polymers and mixtures of two or more thereof. The thermoplastic elastomer can be, for example, styrene-butadiene elastomer (SBE), styrene-butadiene-styrene (SBS) or styrene-butadiene rubber (SBR). An example of an SBS modified bitumen is PmB 25 / 55-55RC.

[0021] Granular material / aggregate

[0022] According to the present invention, the term "granular material" is similarly used to describe components that may also be described as "an aggregate" or "aggregates". In addition, according to the present invention, the granular material or aggregate may include one or more of gravel, sand, filler and fine aggregate. In this regard, additional specific and / or preferred embodiments are disclosed herein.

[0023] Recycled asphalt pavement

[0024] According to the present invention, the terms "reclaimed asphalt pavement" (also abbreviated as RAP), "reclaimed asphalt", "recycled asphalt", "recycled asphalt pavement material" and "recycled asphalt mixture" are similarly used to describe materials that can also be described as "reprocessed pavement containing asphalt and aggregate".

[0025] Asphalt mixture composition / asphalt mixture

[0026] According to the present invention, the terms "asphalt mixture composition" and "asphalt mixture" are used to describe a mixture of aggregate / granular material, recycled asphalt, any type of additives (such as thermosetting reactive compounds, fibers, rejuvenating agents, reactive modifiers, plasticizers, waxes, surfactants, etc.) and asphalt / asphalt base / asphalt composition (modified or unmodified).

[0027] Recycled Asphalt / Recycled Asphalt / Recycled Asphalt Base

[0028] According to the present invention, the term "recycled bitumen" or "recycled bitumen" or "recycled bitumen base" is used to describe bitumen / bitumen base extracted from an asphalt mixture composition. The corresponding recycling process will be described below.

[0029] Elastic response and irreversible creep compliance (J nr) is calculated in a Multiple Stress Creep Recovery (MSCR) test, where the bitumen is subjected to a constant load for a fixed time. The total deformation for a specific time period is given in % and corresponds to a measure of the elasticity of the base material.

[0030] The stiffness of asphalt at low temperatures, commonly referred to as the bending stiffness of asphalt, is determined using a bending beam rheometer (BBR). These parameters give an indication of the ability of the asphalt base to resist cracking at low temperatures. The BBR is used to determine the low temperature grade of the asphalt base.

[0031] Thus, an asphalt composition has been found comprising 0.1-8 wt. % of isocyanate as a thermosetting reactive compound, based on the total weight of the composition, and 0.1-8 wt. % of a plasticizer, based on the total weight of the composition, selected from phthalates, terephthalates, cyclohexanoates, azelates, acetates, butyrates, valerates, alkyl sulfonates, adipates, benzoates, dibenzoates, citrates, maleates, phosphates, sebacates, sulfonamides, epoxy esters, trimellitates, glycerides, succinates, mineral oils and polymer plasticizers or mixtures thereof, wherein the polymer plasticizer is selected from polymers of adipic acid with 2,2-dimethyl-1,3-propanediol and 1,2-propylene glycol isononyl ester, polymers of adipic acid with 1,2-propylene glycol octyl ester and polymers of adipic acid with 1,2-propylene glycol acetate or mixtures thereof.

[0032] According to another aspect of the present invention, there is provided a method for preparing an asphalt composition, comprising the following steps:

[0033] a) heating the starting asphalt to a temperature of 110-190°C,

[0034] b) adding the required amount of isocyanate and the required amount of the respective plasticizer, wherein the order of adding the required additives is not critical, or the respective isocyanates and the respective plasticizers are mixed separately and added as a mixture,

[0035] c) after step b), stirring the reaction mixture at a temperature of 110-190° C. for at least 2 hours, or homogenizing for a period of 2-180 seconds, and optionally

[0036] d) determining the end of the reaction by IR spectroscopy,

[0037] The reaction is carried out under an oxygen atmosphere.

[0038] This achieves the object of the present invention. Furthermore, there is provided the use of the bituminous composition for the preparation of an asphalt mixture composition and the use of the asphalt mixture composition for pavement applications.

[0039] Surprisingly, it was found that bituminous compositions and related asphalt mixture compositions comprising the combination of isocyanate and plasticizer according to the invention show improved rutting resistance, improved fatigue behavior, better elasticity and improved low temperature behavior. In contrast to the prior art rejuvenators, the present invention provides better rutting and fatigue behavior of asphalt mixture compositions containing a high proportion of RAP, and in addition: i) the softening point of base mixtures containing a high proportion of strongly aged bases from RAP is reduced, ii) the compaction temperature of the corresponding asphalt mixture compositions with a high RAP content can be reduced and the workability of the mixture is improved, iii) the resistance of the corresponding asphalt mixture to low temperature cracking is improved.

[0040] Without being bound by this theory, it is currently believed that this is due to the different reactions of isocyanates and plasticizers as thermosetting reactive compounds with the different molecular species of asphaltenes and petroleum greases classified as the corresponding asphalt. A specific morphology of the colloidal structure is required to obtain the resulting properties. The thermosetting reactive compounds will react with phenolic, carboxyl, thiol, anhydride and / or pyrrolyl groups or any reactive groups of the asphalt components and link the asphaltenes together, resulting in larger particles in the resulting asphalt composition. In addition, the plasticizer will modify the petroleum grease phase to promote the formation of an improved colloidal structure of the modified asphalt, resulting in unexpected properties, particularly in terms of improved low temperature cracking resistance of the corresponding asphalt mixture and improved workability of mixtures with high RAP content. Due to the increased stability, this can, for example, provide an opportunity to reduce the size of the subbase, where a large amount of RAP is usually used. This leads to cost and material savings as well as CO 2 Reduction of emissions.

[0041] Preferred embodiments are explained in the claims and the specification. It should be understood that combinations of preferred embodiments are within the scope of the present invention.

[0042] According to the present invention, the asphalt composition comprises an isocyanate as a thermosetting reactive compound and 0.1-8 wt % of a plasticizer based on the total weight of the composition, wherein the plasticizer is selected from phthalates, terephthalates, cyclohexanoates, azelaates, acetates, butyrates, valerates, alkyl sulfonates, adipic acid esters, benzoates, dibenzoates, citrates, maleates, phosphates, sebacates, sulfonamides, epoxy esters, trimellitic acid esters, glycerides, succinates, mineral oils and polymer plasticizers or mixtures thereof, wherein the polymer plasticizer is selected from polymers of adipic acid with 2,2-dimethyl-1,3-propanediol and 1,2-propylene glycol isononyl ester, polymers of adipic acid with 1,2-propylene glycol octyl ester and polymers of adipic acid with 1,2-propylene glycol acetate or mixtures thereof.

[0043] Generally, the asphalt used in the present invention can be any known asphalt, and generally covers any asphalt compound. It can be any material known as asphalt or asphalt base. For example, distilled asphalt, sprayed asphalt, high vacuum asphalt and diluted asphalt, as well as asphalt concrete, poured asphalt, asphalt mastic and natural asphalt. For example, directly distilled asphalt can be used, for example with a penetration of 80 / 100 or 180 / 220. For example, the asphalt can be free of fly ash.

[0044] Preferably, the bitumen has a penetration of 20-30, 30-45, 35-50, 40-60, 50-70, 70-100, 100-150, 160-220, 250-330 or a penetration of 52-16, 52-22, 52-28, 52-34, 52-40, 58-16, 58-22, 58-28, 58-34, 58-40, 64-1 6, 64-22, 64-28, 64-34, 64-40, 70-16, 70-22, 70-28, 70-34, 70-40, 76-16, 76-22, 76-28, 76-34, 76-40 performance grades; more preferably, the asphalt has a performance grade of 30-45, 35-50, 40-60, 50-70, 70-100, 100-15 0, 160-220 needle penetration or 52-16, 52-22, 52-28, 52-34, 52-40, 58-16, 58-22, 58-28, 58-34, 58-40, 64-16, 64-22, 64-28, 64-34, 70-16, 70-22, 70-28, 76-16, 76-22 performance level; most preferably , asphalt has a needle penetration of 40-60, 50-70, 70-100, 100-150 or a performance grade of 52-16, 52-22, 52-28, 52-34, 52-40, 58-16, 58-22, 58-28, 58-34, 64-16, 64-22, 64-28, 70-16, 70-22, 76-16, 76-22.

[0045] Generally, a thermosetting reactive compound is a compound that can chemically react with different molecular species classified as asphaltenes and petroleum fats of the corresponding asphalt and help to generate a colloidal structure of a specific morphology, thereby making the physical properties of the asphalt more constant over a wide temperature range and / or even improving the performance physics within the temperature range experienced by the asphalt.

[0046] According to the present invention, the amount of isocyanate as a thermosetting reactive compound in the asphalt composition is no more than 8.0 wt % based on the total weight of the asphalt composition. Preferably, it is no more than 5.0 wt %, more preferably no more than 4.0 wt %, and most preferably no more than 3.0 wt % based on the total weight of the asphalt composition. According to the present invention, the amount of isocyanate as a thermosetting reactive compound in the asphalt composition is at least 0.1 wt %, preferably at least 0.5 wt %, more preferably at least 0.7 wt %, and most preferably at least 0.9 wt %, based on the total weight of the asphalt composition. For example, the amount of isocyanate as a thermosetting reactive compound in the asphalt composition may be 0.5-3.8 wt %, 0.8-2.7 wt %, 1.0-3.9 wt %, 1.1-2.0 wt %, 1.8-3.2 wt %, 2.1-3.7 wt % or 0.5-3.5 wt %.

[0047] The isocyanate as the thermosetting reactive compound of the present invention can be any isocyanate provided that it is compatible with asphalt, preferably it is toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), polymeric MDI, monomeric MDI, MDI prepolymer, more preferably it is TDI, polymeric MDI, monomeric MDI, most preferably it is polymeric MDI, monomeric MDI, such as polymeric MDI.

[0048] Generally, TDI is known in the art as toluene diisocyanate (TDI). It is an organic compound that exists in different isomers. According to the present invention, any known isomer of TDI or a mixture of different isomers can be used, provided that it is compatible with bitumen. Preferably, it is pure 2,4-TDI or a mixture of 2,4- and 2,6-TDI, more preferably it is a mixture of 2,4- and 2,6-TDI isomers, for example an 80 / 20 or 65 / 35 mixture of 2,4- or 2,6-TDI isomers.

[0049] Generally, HDI is known in the art as hexamethylene diisocyanate (HDI), which is an aliphatic diisocyanate. According to the present invention, any known HDI may be used, provided that it is compatible with the bitumen.

[0050] Typically, MDI prepolymers are known in the art and are the reaction product of polymeric MDI and a polyol. Polymeric MDI as part of an MDI prepolymer is known in the art and is referred to as polymethylene polyphenylene polyisocyanate, also referred to as polyarylene polyisocyanate or polyphenylene methane sodium polyisocyanate. It may contain different amounts of isomers, such as 4,4'-, 2,2'- and 2,4'-isomers. Preferably, the amount of 4,4'-MDI isomer is 26-98%, more preferably 30-95%, most preferably 35-92%. Preferably, the 2-ring content of polymeric MDI is 20-62%, more preferably 26-48%, most preferably 26-42%. It may also include modified variants containing carbodiimide, uretonimine, isocyanurate, urethane, allophanate, urea or biuret groups. All of this is referred to hereinafter as pMDI. The polyol used to prepare the prepolymer is any polyol that can be used in the art, provided that it is compatible with asphalt. Any high molecular weight polyol used in the present invention can be used, which can be any polyol or mixture thereof for preparing polyurethane, and its average hydroxyl equivalent is at least 50, preferably 50-10000, more preferably 500-5000. These polyols can be polyether polyols, polyester polyols, polyesteramide polyols, polythioether polyols, polycarbonate polyols, polyacetal polyols, polyolefin polyols, etc. Preferred polyols are polyethers (especially polypropylene glycol), polyesters (especially aromatic polyesters) and polyolefins (especially polybutadiene) polyols. The functionality of the polyol is preferably 2-4, more preferably 2-3, and most preferably 2. A particularly preferred polyol is polypropylene glycol (PPG), such as PPG2000. Prepolymers can be prepared using methods known to those skilled in the art. The NCO value of the prepolymer can vary over a wide range. It can be about 6-30, preferably about 9-25. The polyol / pMDI ratio may vary in practice from 2 / 98 to 80 / 20 by weight.

[0051] Generally, polymeric MDI is known in the art and is referred to as polymethylene polyphenylene polyisocyanate, also known as polyarylene polyisocyanate or polyphenylene methane sodium polyisocyanate. It may contain different amounts of isomers, such as 4,4'-, 2,2'- and 2,4'-isomers. Preferably, the amount of 4,4'-MDI isomer is 26-98%, more preferably 30-95%, most preferably 35-92%. Preferably, the 2-ring content of polymeric MDI is 20-62%, more preferably 26-48%, most preferably 26-42%.

[0052] It may also include modified variants containing carbodiimide, uretonimine, isocyanurate, carbamate, allophanate, urea or biuret groups. All of this is hereinafter referred to as pMDI. Preferably, the pMDI used in the present invention has an average isocyanate functionality of at least 2.3, more preferably at least 2.5, most preferably at least 2.7, for example 2.8, 2.9 or 3.0.

[0053] Generally, the purity of polymeric MDI is not limited to any value, and preferably the pMDI used in the present invention has an iron content of 1-100 ppm, more preferably 1-70 ppm, and most preferably 1-60 ppm.

[0054] Generally, monomeric MDI (mMDI) is known in the art and is called methylene diphenyl diisocyanate. It can exist in the form of different isomers, such as 4,4'-, 2,2'- and 2,4'-isomers. According to the present invention, any known isomer of mMDI or a mixture of different isomers can be used, provided that it is compatible with bitumen. Preferably, it is pure 4,4'-MDI, a mixture of 2,4'-MDI and 4,4'-MDI, a mixture of 2,2'-MDI and 4,2'-MDI with a reduced 2,4'-MDI content, more preferably pure 4,4'-MDI, a mixture of 2,4'-MDI and 4.4'-MDI, most preferably pure 2,4'-MDI. Preferably, the amount of 4,4'-MDI isomer is 40-99.5%, more preferably 44-99%, most preferably 46-98.5%.

[0055] It can also include modified variants containing carbodiimide, uretonimine, isocyanurate, carbamate, allophanate, urea or biuret groups. All this is hereinafter referred to as mMDI. Preferably, the mMDI used in the present invention has an average isocyanate functionality of at least 2.0, more preferably at least 2.1, most preferably at least 2.15, for example 2.2, 2.3 or 2.4.

[0056] Generally, a plasticizer is an additive that increases the plasticity of a material or reduces the viscosity of a material and changes its physical properties. It reduces the attraction between polymer chains, making it more flexible. According to the present invention, any known plasticizer can be used, provided that it is compatible with asphalt.

[0057] Preferably, the plasticizer is selected from phthalates, terephthalates, cyclohexanoates, azelaates, acetates, butyrates, valerates, alkyl sulfonates, adipates, benzoates, dibenzoates, citrates, maleates, phosphates, sebacates, sulfonamides, epoxy esters, trimellitates, glycerides, succinates, mineral oils and polymer plasticizers or mixtures thereof, wherein the polymer plasticizer is selected from polymers of adipic acid with 2,2-dimethyl-1,3-propanediol and 1,2-propylene glycol isononyl ester, polymers of adipic acid with 1,2-propylene glycol octyl ester and polymers of adipic acid with 1,2-propylene glycol acetate or mixtures thereof.

[0058] Most preferably, the plasticizer is selected from phthalates, terephthalates, cyclohexanoates, alkyl sulfonates, adipates, benzoates, citrates, maleates and mineral oils or mixtures thereof.

[0059] Preferred phthalates may be diisononyl phthalate (DINP), diisodecyl phthalate (DIDP), di(2-propylheptyl)phthalate (DPHP), di(2-ethylhexyl)phthalate (DEHP), dibutyl phthalate (DBP), diisobutyl phthalate (DIBP), benzyl butyl phthalate (BBP) or mixtures thereof. The most preferred phthalate may be diisononyl phthalate (DINP).

[0060] The preferred terephthalate ester may be di(2-ethylhexyl)terephthalate (DEHTP), diisobutyl terephthalate (DBT) or a mixture thereof. The most preferred terephthalate ester may be di(2-ethylhexyl)terephthalate (DEHTP).

[0061] The most preferred cyclohexanoate may be diisononyl-1,2-cyclohexanedicarboxylate (DINCH).

[0062] The preferred azelaic acid ester may be di(2-ethylhexyl) azelate, diisodecyl azelate (DIDA) or a mixture thereof. The most preferred azelaic acid ester may be diisodecyl azelate (DIDA).

[0063] Preferred acetate may be 2-ethoxyethyl acetate, triacetin or a mixture thereof. Most preferred acetate may be triacetin.

[0064] The preferred butyrate may be 1,2,3-propanetriol tributyrate (tributyrin), 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TXIB) or a mixture thereof. The most preferred butyrate may be 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TXIB).

[0065] The most preferred valeric acid ester may be pentaerythritol valeric acid ester (PETV)

[0066] The most preferred alkyl sulfonate may be phenol (C 10 -C 21 )-alkyl sulfonate.

[0067] Preferred adipate esters may be diethylhexyl adipate (di(2-ethylhexyl) adipate) (DEHA), diisononyl adipate (di(7-methyloctyl) adipate) (DINA), diisodecyl adipate (DIDA) or mixtures thereof. The most preferred adipate ester may be diisononyl adipate (di(7-methyloctyl) adipate) (DINA).

[0068] The preferred benzoic acid ester may be isononyl benzoate (INB), isodecyl benzoate (IDB) or a mixture thereof. The most preferred benzoic acid ester may be isononyl benzoate (INB).

[0069] Preferred dibenzoates may be triethylene glycol dibenzoate, dipropylene glycol dibenzoate, neopentyl glycol dibenzoate or a mixture thereof. The most preferred dibenzoate may be dipropylene glycol dibenzoate.

[0070] The preferred citrate ester may be acetyl tributyl citrate (ATBC), tributyl citrate (TBC), triethyl citrate (TEC) or a mixture thereof. The most preferred citrate ester may be acetyl tributyl citrate (ATBC).

[0071] The most preferred maleate may be dibutyl maleate.

[0072] The preferred phosphoric acid ester may be triphenyl phosphate (TPP), tri(2-ethylhexyl) phosphate (TEHP) or a mixture thereof. The most preferred phosphoric acid ester may be tri(2-ethylhexyl) phosphate (TEHP).

[0073] The preferred sebacic acid ester may be dimethyl sebacate (DMS), di(2-ethylhexyl) sebacate, dibutyl sebacate (DBS) or a mixture thereof. The most preferred sebacate may be dimethyl sebacate (DMS).

[0074] The most preferred sulfonamide may be N-butylbenzenesulfonamide (BBSA).

[0075] The preferred epoxy ester may be epoxidized soybean oil (ESBO), epoxidized linseed oil (ELO) or a mixture thereof. The most preferred epoxy ester may be epoxidized linseed oil (ELO).

[0076] The most preferred trimellitic acid ester may be tri(2-ethylhexyl) trimellitate (TOTM).

[0077] The most preferred glyceride may be fully acetylated monoglyceride.

[0078] The preferred succinate ester may be diethyl succinate (DES), dimethyl succinate (DMS) or a mixture thereof. The most preferred succinate ester may be diethyl succinate (DES).

[0079] The polymer plasticizer is selected from the polymer of adipic acid with 2,2-dimethyl-1,3-propanediol and 1,2-propylene glycol isononyl ester, the polymer of adipic acid with 1,2-propylene glycol octyl ester and the polymer of adipic acid with 1,2-propylene glycol acetate or a mixture thereof. The most preferred polymer plasticizer may be the polymer of adipic acid with 2,2-dimethyl-1,3-propanediol and 1,2-propylene glycol isononyl ester.

[0080] Preferably, the plasticizer is selected from the group consisting of diisononyl phthalate, diisodecyl phthalate, di(2-propylheptyl)phthalate, di(2-ethylhexyl)phthalate, di(2-ethylhexyl)terephthalate, dibutyl phthalate, diisobutyl phthalate, benzyl butyl phthalate, diisobutyl terephthalate, diisononyl 1,2-cyclohexanedicarboxylate and phenol. 10 -C 21 )-alkyl sulfonate or a mixture thereof.

[0081] More preferably, the plasticizer is selected from di(2-ethylhexyl) terephthalate, phenol (C 10 -C 21 )-alkyl sulfonate and diisononyl-1,2-cyclohexanedicarboxylate or a mixture thereof.

[0082] Most preferably, the plasticizer is diisononyl 1,2-cyclohexanedicarboxylate (DINCH).

[0083] According to the present invention, the amount of plasticizer or plasticizer mixture in the asphalt composition is no more than 8.0 weight %, based on the total weight of the asphalt composition. Preferably, it is no more than 5.0 weight %, more preferably no more than 4.0 weight %, and most preferably no more than 3.0 weight %, based on the total weight of the asphalt composition. According to the present invention, the amount of plasticizer or plasticizer mixture in the asphalt composition is at least 0.1 weight %, preferably at least 0.5 weight %, more preferably at least 0.7 weight %, and most preferably at least 0.9 weight %, based on the total weight of the asphalt composition. For example, the amount of plasticizer or plasticizer mixture in the asphalt composition can be 0.5-3.8 weight %, 0.8-2.7 weight %, 1.0-3.9 weight %, 1.1-2.0 weight %, 1.8-3.2 weight %, 2.1-2.7 weight % or 0.5-3.5 weight %.

[0084] Other optional additives known in the art may be added to the composition of the present invention in order to adjust the properties of the asphalt composition according to the respective application. The additive may be, for example, a wax. If used as an additional additive in the asphalt base composition, these waxes may be functionalized or synthetic waxes, or naturally occurring waxes. In addition, the wax may be oxidized or non-oxidized. Non-exclusive examples of synthetic waxes include ethylene bis stearamide wax (EBS), Fischer-Tropsch wax (FT), oxidized Fischer-Tropsch wax (FTO), polyolefin waxes such as polyethylene wax (PE), oxidized polyethylene wax (OxPE), polypropylene wax, polypropylene / polyethylene wax, alcohol wax, silicone wax, petroleum waxes such as microcrystalline wax or paraffin and other synthetic waxes. Non-exclusive examples of functionalized waxes include amine waxes, amide waxes, ester waxes, carboxylic acid waxes and microcrystalline waxes. Naturally occurring waxes may come from plants, animals, minerals or other sources. Non-exclusive examples of natural waxes include vegetable waxes such as candelilla wax, carnauba wax, rice wax, Japan wax and jojoba oil; animal waxes such as beeswax, lanolin and spermaceti; and mineral waxes such as montan wax, ozokerite and ceresin. Mixtures of the above waxes are also suitable, for example, the wax may include a mixture of Fischer-Tropsch (FT) wax and polyethylene wax.

[0085] Antioxidants may be used in conventional amounts as additional additives to asphalt base compositions in order to prevent oxidative degradation of polymers which would lead to a loss of strength and flexibility of these materials.

[0086] Conventional amounts of optional additives are 0.1-5% by weight, based on the total amount of the respective bituminous composition. For example, conventional amounts are 0.2-3% by weight, 0.5-2.8% by weight or 0.6-2.5% by weight.

[0087] Typically, the amount of isocyanate and the amount of plasticizer as thermosetting reactive compounds may depend on the composition of the corresponding asphalt. For hard asphalts with a penetration of less than 85, less thermosetting reactive compounds such as pMDI may be required; while for soft asphalts with a penetration of more than 85, a larger amount of corresponding thermosetting active compounds such as pMDI may be required. Without being bound by this theory, it is currently believed that due to the different concentrations of asphaltenes in different asphalts, the amount of thermosetting reactive compounds needs to be readjusted. In soft asphalts corresponding to penetrations higher than 85, the asphaltenes are diluted and therefore have a lower concentration, which requires a larger amount of corresponding thermosetting reactive compounds such as pMDI and more oxidation (which can be provided by the oxygen atmosphere of the asphalt composition preparation process) to obtain better performance. The same situation can be imagined for the petroleum grease phase of each asphalt that is believed to interact with the corresponding polymer.

[0088] Typically, for asphalts with a needle penetration below 85 (corresponding to a performance grade with a high temperature limit of at least 64), the amount of isocyanate selected from polymeric MDI, epoxy resins and melamine-formaldehyde resins as thermosetting reactive compounds in the asphalt composition may be 0.1-3.0% by weight, preferably the amount of thermosetting reactive compounds does not exceed 2.5% by weight, most preferably does not exceed 2.3% by weight, in particular does not exceed 2% by weight, and the amount of thermosetting reactive compounds is at least 0.1% by weight, preferably at least 0.5% by weight, more preferably at least 0.7% by weight, and most preferably at least 1.0% by weight, based on the total weight of the asphalt composition.

[0089] Typically, for asphalts having a needle penetration higher than 85 (corresponding to a performance grade with a high temperature limit of 64 or less), the amount of thermosetting reactive compounds selected from polymeric MDI, epoxy resins and melamine-formaldehyde resins in the asphalt composition may be 2.0-10.0% by weight, preferably, the amount of thermosetting reactive compounds does not exceed 5.0% by weight, most preferably does not exceed 4.5% by weight, in particular does not exceed 4% by weight, and the amount of thermosetting reactive compounds is at least 2.0% by weight, preferably at least 2.5% by weight, more preferably at least 2.7% by weight, and most preferably at least 3.0% by weight, based on the total weight of the asphalt composition.

[0090] In addition to the above, the amount of plasticizer can also be adjusted according to the characteristics of the asphalt used. The weight percentage ratio of isocyanate as a thermosetting reactive compound to plasticizer can be 80:1 to 1:80, preferably 10:1 to 10:10, more preferably 5:1 to 1:5, most preferably 3:1 to 1:3, such as 2:1 to 1:2 or 1:1.

[0091] Generally, by modifying the bitumen, the performance in terms of different physical properties can be improved, for example an increased elastic response can be achieved.

[0092] The combination of isocyanate and plasticizer as additives in bitumen results in a synergistic effect, which means that bitumen comprising the combination of isocyanate and plasticizer surprisingly shows better properties than bitumen comprising only each individual component.

[0093] The bituminous composition of the present invention can be used as any classical bituminous composition in the prior art. The bituminous composition of the present invention can be used in particular for the production of:

[0094] - paints and coatings, especially for waterproofing,

[0095] - Putty for filling joints and sealing cracks,

[0096] - For grouting and hot pouring of surface leveling for roads, airports, sports fields, etc.

[0097] - Mixed with stone to provide aggregate (about 5-20% of the asphalt composition), e.g.

[0098] - Thermal coatings for the above mentioned surface smoothing,

[0099] -Surface coating for smooth surface as above,

[0100] - bitumen emulsion,

[0101] - Warm mix asphalt (WMA),

[0102] -Hot Mix Asphalt (HMA).

[0103] Furthermore, the present invention relates to a method for preparing the bituminous composition of the present invention, comprising the following steps:

[0104] a) heating the starting asphalt to a temperature of 110-190°C,

[0105] b) adding the required amount of isocyanate and the required amount of the corresponding plasticizer, wherein the order of adding the required additives is not critical, or the corresponding isocyanate and the corresponding plasticizer are mixed separately and added as a mixture,

[0106] c) after step b), stirring the reaction mixture at a temperature of 110-190° C. for at least 2 hours, or homogenizing for a period of 2-180 seconds, and

[0107] Optionally

[0108] d) determining the end of the reaction by IR spectroscopy,

[0109] The reaction is carried out under an oxygen atmosphere.

[0110] For example, the method of the present invention can be carried out at a temperature of 110-190° C. in step a) and / or step c). Preferably, the temperature is 110-180° C., more preferably 115-170° C., most preferably 120-165° C., for example 121-162° C.

[0111] Typically, the temperature in steps a), b) and c) is 110-190°C, and the temperature in each step may be different. Preferably, the temperature in each of the three steps is the same and is 110-190°C; more preferably, the temperature is the same and is 110-170°C; most preferably, the temperature is the same and is 110-165°C.

[0112] According to the present invention, in step b) of the method for preparing an asphalt composition, a desired amount of isocyanate as a thermosetting reactive compound and a desired amount of plasticizer are added under stirring. The isocyanate may be added first and then the desired amount of plasticizer, or vice versa. The isocyanate and the plasticizer may be added simultaneously or in the form of a mixture under stirring. The desired amount may be 0.1-8% by weight based on the total weight of the composition of the two components.

[0113] Typically, this amount can also be determined by potentiometric titration, where the number of reactive groups in the bitumen is determined and related to the equivalent weight of reactive groups of the corresponding thermosetting compound. Titration methods are known in the art.

[0114] Typically, bitumen from different suppliers differs in composition, depending on which reservoir the crude oil comes from, and the distillation process of the refinery. However, the cumulative total amount of reactive groups of isocyanates as thermosetting reactive compounds can be 3.1-4.5 mg KOH / g.

[0115] For example, a bitumen with a penetration index of 50-70 or 70-100 results in a stoichiometric amount of pMDI of 0.8-1.2 wt%. Further excess isocyanate will be available to react with newly formed functional groups due to the oxidation sensitivity of the bitumen components at elevated temperatures during the preparation of the bitumen composition.

[0116] According to the present invention, process step c) is carried out after step b). The reaction mixture is stirred at a temperature of 110-190°C for at least 2 hours, preferably the mixing time is at least 2.1 hours, more preferably the mixing time is at least 2.2 hours, and most preferably the mixing time is at least 2.5 hours. After stirring at a temperature of 110-190°C for at least 2 hours, the crosslinking reaction of the reactive groups of the thermosetting compound and the reactive groups of the asphalt and the oxidative crosslinking reaction are completed. In order to complete the crosslinking reaction, at least 2 hours, preferably at least 2.1 hours, more preferably at least 2.2 hours, and most preferably at least 2.5 hours are required.

[0117] As an alternative, the reaction mixture can be homogenized at a temperature of 110-190°C for a period of 2-180 seconds, preferably 2-60 seconds, more preferably 5-40 seconds, more preferably 8-30 seconds, more preferably 10-25 seconds, most preferably 12-20 seconds. Homogenization is achieved with the aid of one or more dynamic mixing elements, more preferably with the aid of one or more circulation pumps and / or high shear mixers and / or one or more agitators and / or one or more screws, more preferably with the aid of one or more agitators. During the homogenization process of the thermosetting reactive compound, the plasticizer and the corresponding bitumen, the crosslinking reaction of the reactive groups is only induced and not finally completed.

[0118] The completion of the crosslinking reaction takes place in a method for preparing an asphalt mixture composition (2), wherein a mixture of the corresponding bitumen and a thermosetting reactive compound and a plasticizer (1) is added to the granular material, for example at a temperature of 110-240° C. and homogenized again for a period of 5-180 seconds. This method is known in the art and is described in detail in, for example, EP 19198042.4. Due to the high surface area of ​​the granular material, the completion of the crosslinking reaction under stirring is faster than other alternatives.

[0119] Preferably, the addition in (2) is achieved by injecting at least a portion of the mixture (1) into at least a portion of the granular material. Particularly preferably, the addition in (2) is achieved by injecting at least a portion of the mixture (1) into at least a portion of the granular material by means of a dosing pump.

[0120] Preferably, the homogenization in (2) is achieved by means of one or more dynamic mixing elements, more preferably by means of one or more agitators and / or one or more screws, more preferably by means of a twin-shaft forced mixer (twin-shaft paddler).

[0121] Preferably, the homogenization in (2) is carried out in a mixing device. Particularly preferably, the mixing device is part of an asphalt mixing plant.

[0122] In case the homogenization in (2) is carried out in a mixing apparatus, the granular material is preferably added to the mixing apparatus before the bituminous mixture (1) is added.

[0123] Preferably, in (2), adding and homogenizing are performed simultaneously.

[0124] Preferably, (c) and / or (2), more preferably (c) and (2), are carried out as a batch process or as a continuous process. Particularly preferably, (c) and / or (2), more preferably (c) and (2), are carried out as a continuous process.

[0125] According to the present invention, the method for preparing an asphalt composition and the method for preparing an asphalt mixture composition (2) must be carried out in an oxygen atmosphere. Preferably, the oxygen concentration in the oxygen atmosphere is 1-21% by volume; more preferably, the oxygen concentration in the oxygen atmosphere is 5-21% by volume; most preferably, the oxygen concentration in the oxygen atmosphere is 10-21% by volume, for example, the method of the present invention is carried out in air or an oxygen-saturated atmosphere.

[0126] The method of the present invention is not limited to a specific bitumen as starting material, which means that commercially available polymer modified bitumen (PmA) can also be further modified by the method of the present invention by adding isocyanates and polymers as thermosetting compounds to PmA or diluting PmA with virgin bitumen and using it as starting material for the modification method of the present invention. Commercially available PmA can also be mixed with the modified bitumen synthesized according to the method of the present invention.

[0127] Generally, the method is not limited to being carried out in one reaction vessel, such as a container. Under the above conditions, for example at a temperature of 110-190° C. under oxygen conditions, the corresponding bitumen can be reacted in a first step with an isocyanate and a plasticizer as thermosetting reactive compounds. The bitumen is then cooled and transferred to a different reaction vessel after transfer heating, thereby completing the total reaction time under oxygen.

[0128] Furthermore, the present invention relates to the use of the bituminous composition for the preparation of an asphalt mixture composition and for pavement applications.

[0129] Preferably, the granular material providing an asphalt mixture composition using the asphalt composition of the present invention comprises 5-100 wt% of reclaimed asphalt pavement based on 100 wt% of the granular material; wherein more preferably, the granular material comprises 10-90 wt%, more preferably 15-80 wt%, more preferably 20-70 wt%, more preferably 25-60 wt%, more preferably 30-50 wt%, more preferably 35-45 wt% of reclaimed asphalt pavement, based on 100 wt% of the granular material.

[0130] Examples of the bituminous composition of the present invention

[0131] Z1: 1.2-3.5 wt % of pMDI as a thermosetting reactive compound, based on the total weight of the composition, and 1.5-3.2 wt % of DINCH, based on the total weight of the composition.

[0132] Z2: 1.2-3.5 wt% of pMDI as a thermosetting reactive compound, based on the total weight of the composition, and 0.5-2.2 wt% of di(2-ethylhexyl) terephthalate, based on the total weight of the composition.

[0133] Z3: 1.0-2.0 wt% of pMDI as a thermosetting reactive compound based on the total weight of the composition, and 2.0-3.2 wt% of phenol based on the total weight of the composition (C 10 -C 21 )-alkyl sulfonate.

[0134] Z4: 1.0-2.3 wt % of pMDI as a thermosetting reactive compound, based on the total weight of the composition, and 0.5-1.5 wt % of DINCH, based on the total weight of the composition.

[0135] Z5: 1.2-3.5 wt% of mMDI as a thermosetting reactive compound, based on the total weight of the composition, and 1.5-3.2 wt% of di(2-ethylhexyl) terephthalate, based on the total weight of the composition.

[0136] Z6: 1.2-3.5 wt% of mMDI as a thermosetting reactive compound based on the total weight of the composition, and 0.5-2.2 wt% of phenol based on the total weight of the composition (C 10 -C 21 )-alkyl sulfonate.

[0137] Examples and Comparative Examples

[0138] Characterization methods

[0139] a) Asphalt testing

[0140] Softening point according to DIN EN 1427 ("Ring and Ball Method")

[0141] Two horizontal asphalt disks cast in shouldered brass rings are heated at a controlled rate in a liquid bath while each disk supports a steel ball. The softening point is reported as the average temperature at which the two disks soften enough to allow each ball encased in asphalt to fall a distance of 25 ± 0.4 mm.

[0142] Rotating Thin Film Oven Test (RTFOT or RTFO Test) according to DIN EN 12607-1

[0143] The bitumen is heated in an oven at 163°C in cylindrical glass bottles for 75 minutes (8 bottles can be used per run). The bottles rotate at 15 rpm and heated air is blown into the lowest point of each bottle at a rate of 4000 mL / min. The influence of heat and air is determined by the change in the physical test values ​​measured before and after the oven treatment. The RTFO test simulates aging during production (mixing), transport of the mix and pouring / paving (= short-term aging of the asphalt base).

[0144] Pressure Ageing Vessels (PAV) according to DIN EN 14769

[0145] The samples that have undergone short-term aging according to the RTFO test are placed in standard stainless steel pans and aged for 20 hours at a specified conditioning temperature (90°C, 100°C or 110°C) in a container pressurized to 2.10 MPa with air. The temperature is selected according to the grade of the asphalt base (application). Finally, the samples are vacuum degassed. This test simulates aging during the service life (long-term aging).

[0146] Dynamic Shear Rheometer (DSR) according to DIN EN 14770, ASTM D7175

[0147] The dynamic shear rheometer test system consists of parallel plates, a device to control the temperature of the specimen, a loading device, and a control and data acquisition system. It is used to determine the rheological properties of asphalt base materials. The complex shear modulus is an indicator of the stiffness of the asphalt base material or its ability to resist deformation under load. The complex shear modulus and the phase angle define the asphalt base material's resistance to shear deformation in the linear viscoelastic region.

[0148] "Bitumen-Typisierungs-Schnell-Verfahren" (BTSV) - Determination of BTSV temperature and BTSV phase angle

[0149] A bituminous base material sample with a diameter of 25 mm is pressed between parallel metal plates at a specified frequency in a DSR device. In this case, one of the parallel plates vibrates relative to the other at 1.59 Hz and an angular deflection amplitude. The temperature is increased at a constant rate of 1.2 ° C / min. The measurement is started at 20 ° C. Heating is carried out at a constant rate until a complex modulus of 15 kPa is reached. The temperature and phase angle at this point are defined as the BTSV temperature (T BTSV , [℃]; can also be used instead of softening point, because T BTSV Related to the hardness of the base material, i.e. a hard base material has a high T BTSV , soft base material has low T BTSV ) and BTSV phase angle (δ BTSV , [°]; is a measure of the elasticity of the base material, i.e. a base material with low elasticity (e.g. paving grade asphalt base material) has a high δ BTSV , while modified base stocks (such as polymer modified asphalt base stocks) have low δ BTSV ).

[0150] ("Das Bitumen-Typisierungs-Schnell-Verfahren", Alisov et al., Straβe und Autobahn, August 2018; "Modifzierung bestimmen", M.Sutor-Fiedle, Asphalt&Bitumen05 / 2017)

[0151] Determination of viscosity of asphalt base

[0152] A bituminous base sample with a diameter of 25 mm is pressed between parallel metal plates at a defined shear rate in a DSR apparatus. The viscosity is determined at 150°C at a shear rate of 10 1 / s.

[0153] Temperature scan according to DIN EN 14770

[0154] This test is designed to measure the complex shear modulus and phase angle of asphalt base materials using a DSR device. A specimen of asphalt base material with a diameter of 8 or 25 mm is pressed between parallel metal plates at a specified frequency and temperature. In this case, one of the parallel plates vibrates with respect to the other at an amplitude of 1.59 Hz and angular deflection. The desired amplitude must be selected so that the test is carried out in the linear behavior region. The procedure is repeated at 30°C, 40°C, 50°C, 60°C, 70°C, 80°C and 90°C.

[0155] Multi-Stress Creep Recovery Test (MSCRT or MSRC test) according to DIN EN 16659, ASTM D7405

[0156] MSCRT is used to determine the presence of an elastic response of an asphalt base under shear creep and recovery at two stress levels (0.1 and 3.2 kPa) at a specified temperature (60°C). This is performed using a DSR apparatus. A 25 mm asphalt base specimen is placed under a constant stress for 1 second and then allowed to recover for 9 seconds. Ten cycles of creep and recovery are performed at a creep stress of 0.100 kPa, followed by 10 cycles at a creep stress of 3.200 kPa.

[0157] Bending Beam Rheometer (BBR) according to DIN EN 14771, ASTM D6648

[0158] The midpoint deflection of an asphalt-based simply supported prismatic beam subjected to a constant load applied to its midpoint was determined. The prismatic specimens were placed in a temperature-controlled fluid bath and loaded with a constant test load for 240 seconds. A computerized data acquisition system was used to monitor the test load (980 ± 50 mN) and the midpoint deflection of the specimen over time. The maximum bending stress at the midpoint of the specimen was calculated from the specimen dimensions, the distance between the supports, and the load applied to the specimen at loading times of 8.0, 15.0, 30.0, 60.0, 120.0, and 240.0 seconds. The stiffness of the specimen for a specific loading time was calculated by dividing the maximum bending stress by the maximum bending strain.

[0159] b) Asphalt mixture composition test

[0160] Cyclic Compression Test (CCT) - According to TP Asphalt-StB Teil 25 B1, DIN EN 12697-25:2016

[0161] A uniaxial cyclic compression test is used to determine the deformation behavior of the asphalt mixture specimens. In this test, the specimens are tempered at 50±0.3°C for 150±10 minutes, which is the same temperature at which the test is carried out. After tempering, the specimens are placed on a universal testing machine and loaded cyclically. Each cycle lasts 1.7 seconds, with a loading time of 0.2 seconds and a pause time of 1.5 seconds. The high load applied is 0.35MPa and the low load is 0.025MPa. The number of cycles and deformation are recorded. The test ends when 10,000 load cycles are completed or the deformation is greater than 40%.

[0162] Indirect tensile strength test - according to TP Asphalt-StB Teil 23, DIN EN 12697-23: 2003

[0163] The fatigue behavior of asphalt mixture specimens is determined by indirect tensile strength testing. This is achieved by loading a cylindrical specimen on its perpendicular diameter plane at a specified deformation rate (50 ± 0.2 mm / min in this case) and test temperature (20 ± 2 °C in this case). The peak load at failure is recorded and used to calculate the indirect tensile strength of the specimen.

[0164] Uniaxial tensile stress test and thermal stress restrained specimen test - according to TP Asphalt-StB Teil 46A (LTT = Low Temperature Test) and DIN EN 12697-46:2012

[0165] The cold behavior of asphalt mixture samples is determined using uniaxial tensile stress tests and thermal stress restrained specimen tests according to European standard EN 12697-46:2012:

[0166] i) Thermal Stress Restrained Specimen Test (TSRST): While the deformation of the specimen is restrained, the temperature is reduced by a predetermined cooling rate.

[0167] ii) Uniaxial Tensile Strength Test (UTST): To assess the risk of low temperature cracking, the stress induced by thermal shrinkage is compared with the corresponding tensile strength.

[0168] Low temperature cracking of asphalt mixture compositions is caused by thermal contraction during cooling, which generates tensile stresses in the asphalt mixture. The low temperature behavior of the pavement layer is simulated by these two tests.

[0169] Rutting test according to TP Asphalt-StB Teil 22 DIN EN 12697-22:2003

[0170] The rutting test determines the deformation (rutting) depth of an asphalt mixture composition subjected to cyclic passage of loaded rubber wheels under constant and controlled temperature conditions. Typically, 10,000 cycles are performed at 50°C.

[0171] Compactability according to TP Asphalt-StB Teil 10 DIN EN 12697-10

[0172] The compactability of the asphalt mixture compositions was determined as follows: According to EN 12697-30, Marshall specimens were prepared from the asphalt mixture and 100 compactions were performed on each side of the specimens. The thickness change was measured after each compaction. Then, a mathematical formula was derived from the experimental results. The corresponding formula parameters allow the compactability of the investigated asphalt mixture composition to be characterized.

[0173] Recycling of asphalt base from asphalt mixture compositions (recycled asphalt / recycled asphalt base)

[0174] With the help of an asphalt analyzer, about 3 kg of the asphalt mixture composition is mixed with trichloroethylene. Aggregates are separated from the asphalt base in a process of about 60 minutes. After completing the procedure, a solution of about 600 mL of trichloroethylene and asphalt is obtained. The solution is then distilled by partially immersing the rotary distillation flask of the rotary evaporator in a heated oil bath while subjecting the solution to a partial vacuum and air flow. The process has two stages. Stage 1 takes 60 minutes and is carried out at 90°C, 40kPa pressure and 75rpm speed. Stage 2 is carried out at 160°C, 2kPa and 75rpm speed. Depending on the type of asphalt base and the asphalt base content of the asphalt mixture, 100-150g of asphalt base is recovered and then tested as needed.

[0175] a) Asphalt base material testing

[0176] Preparation of a long-aged 50 / 70 bituminous base and its mixture with an unaged (pure) base in a ratio of 75:25 (by weight) 70 / 100

[0177] 2 kg of long-term aged asphalt base with a penetration grade of 50 / 70 was prepared by implementing four subsequent RTFOT aging procedures, i.e., aging at 163°C for 4×75 minutes (300 minutes in total), using pure asphalt base with a penetration grade of 50 / 70. One round (300 minutes at 163°C) can prepare 35 g ± 0.5 g of asphalt base / bottle, i.e., 8×35 g = 280 g of long-term aged base. After completing the aging rounds, all long-term aged samples were placed in a tank, heated to 120-140°C, and briefly stirred to achieve homogeneity.

[0178] 1 kg of homogenized long-term aged asphalt base was mixed with pure asphalt base with a penetration grade of 70 / 100. The mixing ratio was 75:25 (long-term aged: pure, by weight). The mixing was carried out at 120-140°C under constant stirring for no more than 1 minute. The mixture was then divided into 120 g portions and used as samples for asphalt base modification.

[0179] Prepare a mixture of isocyanate and plasticizer:

[0180] For asphalt base modification, 150 g of polymeric diphenylmethane diisocyanate with an average isocyanate functionality of 2.7 (hereinafter referred to as "As20") and 350 g of plasticizer (in DINCH) to prepare a mixture of 500 g of isocyanate and plasticizer. The mixture of DINCH is hereinafter referred to as "As20-DINCH mixture".

[0181] General procedure for preparing modified asphalt base compositions

[0182] Asphalt base modification using unaged (neat) 50 / 70 base (Table 1, Sample 2) or a 75:25 mixture (by weight) of long-term aged 50 / 70 base and unaged (neat) 70 / 100 base (Table 1, Samples 5 and 6) was performed as follows:

[0183] 120 g of the corresponding asphalt base was heated to 150° C. under air by placing the sample in a preheated oven. 1.8 g (1.5 wt %, relative to the amount of asphalt base) or 6 g (5.0 wt %, relative to the amount of asphalt base) of As20 or an isocyanate-plasticizer mixture (=3:7 weight ratio of As20: DINCH mixture) was added to the molten asphalt base (see Table 1). The mixture obtained was stirred for a few seconds (<10 seconds) to obtain homogeneity. The sample was then divided into 35 g ± 0.5 g portions for the rotating thin film oven test of short-term aging. This test simulates the mixing process and the subsequent transportation of the asphalt mixture composition to the construction site until the asphalt paving of the asphalt mixture is aged. After aging, the modified bitumen was stored at room temperature or used for the following further tests: Determination of the softening point / BTSV temperature (T BTSV / ℃; can replace softening point), BTSV phase angle (δ BTSV / °) and viscosity (at 150°C) (see Table 1).

[0184] Table 1. Viscosity and T of different asphalt base materials BTSV and δ BTSV .

[0185]

[0186] *Long-term aged asphalt base prepared by four subsequent RTFOT aging cycles (see above)

[0187] The workability of asphalt mixture compositions is directly related to the viscosity of the asphalt base, i.e., high viscosity asphalt bases cause compaction problems during asphalt mixture paving. It is known in the art that aging of asphalt bases leads to an increase in base viscosity and softening point / BTSV temperature. This in turn means that, on the one hand, asphalt mixture compositions containing a high proportion of aged bases (i.e., a high proportion of recycled asphalt pavement (RAP)) are more difficult to compact / process. On the other hand, the increase in softening point / BTSV temperature means that the asphalt mixture becomes harder, i.e., the stability at higher temperatures increases. When observing the BTSV phase angle of the asphalt base, a lower phase angle reflects better performance in terms of flexibility / elasticity / lower brittleness of the asphalt mixture, and therefore better performance. Typically, a BTSV phase angle below 75° is a characteristic of modified asphalt (e.g., polymer modified asphalt; see "Modifzierung bestimmen", M. Sutor Fiedler, Asphalt&Bitumen 05 / 2017).

[0188] As can be seen from Table 1, the modification of the unaged asphalt base 50 / 70 with As20 leads to an increase in viscosity and softening point / BTSV temperature. In addition, the phase angle is reduced. Therefore, it can be expected that each asphalt mixture composition containing this base has better performance.

[0189] Long-term aging of the unmodified asphalt base 50 / 70 (sample 3) leads to a substantial increase in viscosity, especially softening point / BTSV temperature. To counteract this effect, an unmodified softer asphalt base, such as pen 70 / 100, can be added, as shown in sample 4. A weight ratio of 75:25 is a typical ratio for an asphalt mixture composition containing 75% RAP. This mixture is used, for example, for subbases.

[0190] When modifying a 75:25 mixture (by weight) of a long-term aged 50 / 70 base and an unaged (pure) 70 / 100 base (Sample 5), the viscosity and softening point / BTSV temperature are expected to increase and the BTSV phase angle decreases. The viscosity of the corresponding modified base is within the range of polymer modified asphalts. Due to the high viscosity, compaction problems can be expected in asphalt mixtures containing this asphalt base. Surprisingly, it was found that by using a thermosetting reactive compound (As20) in combination with a plasticizer ( DINCH), the viscosity and softening point / BTSV temperature of the asphalt base can be significantly reduced, that is, the workability of the corresponding asphalt mixture (sample 6) is improved. In addition, the phase angle is not negatively affected, that is, the phase angle is only slightly increased compared with sample 5. Interestingly, the BTSV performance characteristics obtained are typical characteristics of polymer modified asphalt (such as PmB 25 / 55-55). Therefore, it is expected that the performance of the asphalt mixture composition containing the base material of this embodiment will be greatly improved, while obtaining good workability of the asphalt mixture, and at the same time, a high proportion of recycled asphalt pavement materials for pavement can be achieved.

[0191] Additional benefits include, for example: lower paving temperatures due to lower viscosity, thus reducing asphalt emissions (asphalt vapor and aerosols), increasing the RAP content of pavement layers where RAP use is limited (e.g., base layers where only 50 wt. % RAP combined with polymer-modified asphalt is allowed), using RAP materials where the base softening point is very high (i.e., RAP materials have fewer age restrictions), and reducing the size of the subbase due to increased stability, thus saving costs and raw materials and reducing CO 2 emission.

[0192] b) Asphalt mixture composition test

[0193] The above-mentioned asphalt base tests using an ideal mixture of unaged and aged asphalt bases have demonstrated the advantages of the As20-DINCH mixture (additive of the present invention). However, the ideal base mixture does not represent the actual conditions existing in asphalt mixture compositions. There, the aged asphalt contained in the RAP material adheres to the aggregates and is not completely and uniformly mixed with the unaged (pure) asphalt base added during the mixing process. Moreover, asphalt performance data do not always reflect the performance of the asphalt mixture. Therefore, tests of asphalt mixture compositions with / without a reference additive were carried out. The reference additive is a prior art rejuvenating agent, which is used to reduce the softening point of the RAP material, restore the material properties and thus enable the use of higher amounts of RAP.

[0194] Procedure for preparing asphalt mixture compositions

[0195] For each of the 4 samples listed in Table 2, two batches were prepared, each with a total mass of 40 kg (=aggregate+RAP material; asphalt base and additives were on top, see Table 2). In the case of Example 1 and Comparative Example 1, the asphalt base 70 / 100 was premixed with the As20-DINCH mixture (additive of the invention) and the reference additive, respectively. The batch size of each premix was 1200 g and was prepared as follows: i) the 70 / 100 asphalt base was melted by heating it to 130-150° C., ii) 972 g of the molten asphalt base was weighed into a separate tank, iii) 228 g of the additive of the invention (As20: DINCH (3:7 mixture) or the reference additive is added to the molten asphalt mixture at 130-150°C under stirring, iv) stirred for less than 1 minute to obtain homogeneity, and v) the prepared premix is ​​then immediately used to prepare the corresponding asphalt mixture composition. The reference additive used is a commonly used and commercially available rejuvenating agent that reduces the softening point of the asphalt base in the asphalt mixture composition containing RAP and the viscosity of the corresponding asphalt mixture composition in order to provide good mix workability during paving.

[0196] Aggregates, RAP, asphalt base / asphalt base additive premix were weighed as indicated in Table 2 for each asphalt mixture composition and then stirred in a laboratory mixer (maximum batch size of 70 kg allowed) at 170° C. for 10 minutes. Aggregate sieving, total asphalt base and RAP content correspond to AC 22TS pavement layer. The asphalt content of the RAP material is 3.8% by weight. The addition amount of 5% by weight is relative to the total asphalt content (bitumen from RAP + unaged (pure) asphalt) of the unmodified variant (see Reference Example 2: 1140 g base from RAP + 404 g pure base 70 / 100). In order to keep the volume of the modified base approximately constant (Example 1 and Comparative Example 1), the amount of pure base is reduced by the amount of additive (i.e., by 76 g compared to Reference Example 2).

[0197] After mixing, 20 kg portions of the prepared asphalt mixture compositions were filled into barrels and stored in an oven at 150°C for 1 hour (the samples were preheated to 150°C before being placed in the oven). After storage, Marshall specimens were prepared for compaction testing. In addition, two asphalt mixture panels were prepared for cyclic compression testing (CCT) and low temperature testing (LTT). The asphalt base properties (T BTSV , δ BTSV The results of the asphalt base and asphalt mixture tests are summarized in Table 3.

[0198] Table 2. Recipes of different asphalt mix compositions. Aggregate sieving, total asphalt base and RAP content correspond to AC22TS pavement layer. The 5 wt.% addition is relative to the total asphalt content (bitumen from RAP + unaged (pure) asphalt) of the unmodified variant given in Reference Example 2. The asphalt content of the RAP material is 3.8 wt.%.

[0199]

[0200] Table 3. Asphalt base and asphalt mixture performance characteristics of the prepared asphalt mixture composition (see Table 2)

[0201]

[0202]

[0203] Asphalt base material properties

[0204] As can be seen from Table 3, if the proportion of RAP increases, the softening point / BTSV temperature of the asphalt base of the asphalt mixture composition increases (compare reference examples 1a and 1b). In addition, the low temperature behavior deteriorates as expected (reaching a stiffness of 300 MPa or an m value of 0.3 at higher temperatures).

[0205] When the As20-DINCH mixture (5 wt%) was used in an asphalt mixture composition containing 75 wt% RAP (Example 1), the softening point / BTSV temperature could be reduced from 69.3°C to 67.8°C. In addition, the BTSV phase angle was greatly reduced from 72.0° to 68.0°, and the low temperature behavior was significantly improved (300 MPa stiffness or 0.3 m value was achieved at lower temperatures compared to Reference Example 1b). Due to the lower BTSV phase angle, the asphalt mixture has better performance in terms of flexibility / elasticity / lower brittleness, so better performance is expected.

[0206] The reference additive (Comparative Example 1) significantly reduces the softening point / BTSV temperature of the asphalt base from 69.3° C. to 60.2° C. The BTSV phase angle increases slightly, i.e. the performance of the corresponding asphalt mixture composition is expected to be worse, not even at the same level as the unmodified variant (Reference Example 1b).

[0207] Asphalt mixture performance

[0208] The test results of asphalt mixture composition are consistent with those of asphalt base material. The following conclusions can be drawn:

[0209] The additive of the invention (As20-DINCH mixture) outperforms the reference additive in the deformation behavior (measured by CCT) of the respective asphalt mixture compositions. The deformation behavior of the asphalt mixture compositions containing the reference additive is even worse than that of the reference example without the additive. This is consistent with the results of the investigation of the base material.

[0210] The low temperature behaviors of Example 1 and Comparative Example 1 are almost at the same level, both being better than the reference example without additives.

[0211] Due to the reduced viscosity of the asphalt base (see asphalt base test results), the additive of the present invention (As20-DINCH mixture) has better compaction at low temperatures (see Table 3, 115°C and 100°C; lower values ​​are associated with better compaction of the asphalt mixture composition) when compared to Reference Example 1b and Comparative Example 1. Therefore, the additive of the present invention (As20-DINCH mixture) improves the workability of the mixture. In addition, the temperature during the production and laying of the asphalt mixture can be reduced.

[0212] c) (Batch) Asphalt Mixing Plant Test

[0213] The laboratory findings were transferred to real-scale by conducting tests in a (batch) asphalt mixing plant, as described below.

[0214] Preparation of an asphalt mixture composition containing 50 wt.% RAP in a (batch) asphalt mixing plant - without additives (Comparative Example 2)

[0215] The batch size is 3500 kg. The particle size curve of the asphalt mixture composition is AC 22BS. The asphalt mixture includes 50% by weight of recycled asphalt (aggregate + asphalt) and 50% by weight of virgin material. The total asphalt content in the asphalt and aggregate mixture is 4.5% by weight, i.e. 157.5 kg of asphalt per 3500 kg batch. 84 kg of the 157.5 kg of asphalt comes from recycled asphalt (4.8% by weight) and the remaining 73.5 kg comes from the addition of unmodified (paving grade) asphalt pen 70 / 100 (according to DIN EN 1426, with a needle penetration of 7-10 mm). The particle size distribution is adjusted as shown in Table 4, where the bypass describes a mixture of virgin granular material (without filler) that complies with the AC 22BS pavement layer and is manually adjusted by the mixing plant operator. The screening and base material content analysis after the asphalt mixture production are shown in Table 5.

[0216] The original granular material and the regenerated asphalt are preheated separately from each other and then mixed together for 6 seconds (premix). The heating power and mixing time are adjusted so that the temperature of the final asphalt mixture composition can reach 140-155°C. 73.5kg of unmodified (paving grade) asphalt pen70 / 100 preheated to a temperature of 165-175°C is weighed into an asphalt balance. Asphalt and premixed materials (a mixture of original aggregate and regenerated asphalt, temperature ≤ 170°C) are added to a mixing unit (a twin-shaft forced mixer) and the resulting mixture is further mixed, wherein the total duration of further mixing is 30 seconds. At this stage of the process, the temperature of the resulting final asphalt mixture composition is measured to be 145-150°C. Subsequently, the asphalt mixture composition is released into a silo and then directly enters a wheel loader (i.e., no storage time). Subsequently, sampling is performed to perform asphalt base material testing (carried out after asphalt base material recovery as described above) and asphalt mixture composition testing (Table 6).

[0217] Preparation of an asphalt mixture composition containing 50 wt. % RAP in a (batch) asphalt mixing plant - using 5 wt. % As20-DINCH mixture (additive according to the invention) (Example 2)

[0218] The asphalt mixing plant is equipped with a customized feeding system (heatable feeding line, feeding pump) allowing the additive of the invention (As20: INCH) is added to the asphalt balance (mixing vessel) of the asphalt mixing plant. In addition, the asphalt balance is equipped with an agitator, which is engaged when i) the As20-DINCH mixture is added and ii) the minimum filling level of 20 kg of asphalt is reached. The additive dosing amount and rate as well as the mixing are controlled by the process control system of the asphalt mixing plant.

[0219] The batch size is 3500 kg. The particle size curve of the asphalt mixture composition is AC 22BS. The asphalt mixture comprises 50% by weight of recycled asphalt (aggregate + asphalt) and 50% by weight of virgin material. The total asphalt content in the asphalt and aggregate mixture (including additives, as they can modify the base material) is 4.5% by weight, i.e. 157.5 kg of (modified) asphalt per 3500 kg batch. 84 kg of the 157.5 kg of asphalt comes from recycled asphalt (4.8% by weight), 65.5 kg comes from the addition of unmodified (paving grade) asphalt pen70 / 100 (according to DIN EN 1426, with a needle penetration of 7-10 mm), and 8.0 kg of As20-DINCH mixture is added. The amount of additive is calculated based on the unmodified variant given in comparative example 2, i.e. 5.0 wt. % (= bitumen from recycled asphalt + added unmodified (paving grade) asphalt pen70 / 100 = 157.5 kg) relative to the total (unmodified) base. In order to keep the volume of the modified base of example 2 approximately constant, the amount of pure base is reduced by the amount of As20-DINCH mixture, i.e. 8.0 kg compared to comparative example 2.

[0220] The particle size distribution was adjusted as shown in Table 4, where the miscellaneous material describes the mixture of raw granular material (without filler) that complies with the AC 22BS pavement layer and is adjusted manually by the plant operator. The screening and base content analysis of the asphalt mix after production are shown in Table 5.

[0221] The original granular material and the recycled asphalt are preheated separately from each other and then mixed together for 6 seconds (premix). The heating power and mixing time are adjusted so that the temperature of the final asphalt mixture composition can reach 140-155°C. 65.5kg of unmodified (paving grade) asphalt pen 70 / 100 preheated to a temperature of 165-175°C is weighed into a mixing container (= asphalt balance). Then 8.0kg of As20-DINCH mixture is added to the asphalt under stirring (1500rpm), and then the resulting mixture is further stirred, wherein the feed rate is set to 0.1-2.0L / s, and the further stirring time is set to 10 seconds. The resulting modified asphalt is added to a mixing unit (twin-shaft forced mixer) together with a premixed material (a mixture of original aggregate and recycled asphalt, with a temperature of ≤170°C) and the resulting mixture is further mixed, wherein the total duration of further mixing is 30 seconds. At this stage of the process, the temperature of the resulting final asphalt mixture composition is measured to be 145-150°C. Subsequently, the asphalt mixture composition was released into a silo and then directly into a wheel loader (ie no storage time). Subsequently, samples were taken for asphalt base testing (performed after asphalt base recovery as described above) and asphalt mixture composition testing (Table 6).

[0222] Table 4. Asphalt mixture compositions prepared in a (batch) asphalt mixing plant with or without the additive of the invention (As20: DINCH (3:7 mixture).

[0223]

[0224] Table 5. Sieve analysis and asphalt base content of the prepared asphalt mix compositions.

[0225]

[0226] Table 6. Asphalt mixture composition tests and asphalt base tests, performed using samples prepared in a (batch) asphalt mixing plant, with and without the additive according to the invention (As20: DINCH (3:7 mixture).

[0227]

[0228] Asphalt base material properties

[0229] When the additive according to the invention (As20-DINCH mixture) was used in an asphalt mixture composition containing 50 wt.% RAP (Example 2) in an asphalt mixing plant, the BTSV temperature increased from 54.6°C to 61.7°C (Table 6). Thus, the relatively low softening point is increased, resulting in a better stability of the asphalt mixture at high temperatures (Example 2), while the rather high softening point (see Example 1 and Reference Example 1b above) is reduced, resulting in a softer material. In addition, the BTSV phase angle is significantly reduced from 75.9° to 66.5°, and the low temperature behavior remains at a similar level (see Reference Example 2). Due to the lower BTSV phase angle, the asphalt mixture has better properties in terms of flexibility / elasticity / lower brittleness, and therefore better performance is expected. In addition, J nr The value (by means of MSCR test) is reduced from 1.55 1 / kPa to 0.26 1 / kPa, i.e. the base material is now specially designed for extreme traffic loads (> 30 million ESAL and J nr <0.5 when the fixed traffic volume; 1ESAL (equivalent uniaxial load) = 80kN), rather than only for the heavy load used in Comparative Example 2 (10-30 million ESALs or J nr <2 hours of slow traffic).

[0230] Asphalt mixture performance

[0231] From the asphalt mixture performance tests (Hamburg rutting test, compaction, CCT, LTT), it can be seen that the present invention (As20-DINCH mixture) is significantly superior to the comparative example (Table 6): better compaction / workability of the mixture, better rutting and fatigue behavior, better low temperature performance. This is consistent with the above-mentioned asphalt base test results. Interestingly, in contrast to the asphalt base test, the low temperature performance determined by the asphalt mixture low temperature test (LTT) can even be improved, as the fracture temperature is reduced from -26.4°C to -31.2°C.

[0232] In conclusion, both the asphalt base tests and the asphalt mixture composition tests confirmed the results of the industrial-scale laboratory studies and demonstrated the performance and advantages of the additive of the present invention (As20-DINCH mixture).

Claims

1. An asphalt composition comprising 0.1-8 wt % of isocyanate as a thermosetting reactive compound based on the total weight of the composition and 0.1-8 wt % of a plasticizer based on the total weight of the composition, wherein the plasticizer is diisononyl-1,2-cyclohexanedicarboxylate.

2. The asphalt composition of claim 1, wherein the isocyanate has a functionality of at least 2.

0.

3. The asphalt composition according to claim 1, wherein the isocyanate is selected from the group consisting of monomeric MDI, polymeric MDI, MDI prepolymers, TDI and HDI.

4. The asphalt composition according to claim 2, wherein the isocyanate is selected from the group consisting of monomeric MDI, polymeric MDI, MDI prepolymers, TDI and HDI.

5. The bituminous composition according to any one of claims 1 to 4, wherein the isocyanate is polymeric MDI.

6. The bituminous composition according to claim 5, wherein the polymeric MDI has a viscosity of 10-5000 cps / mpas at 25°C.

7. The bituminous composition according to claim 5, wherein the amount of polymeric MDI is 0.5-5.0 wt. %, based on the total weight of the composition.

8. The bituminous composition according to claim 6, wherein the amount of polymeric MDI is 0.5-5.0 wt. %, based on the total weight of the composition.

9. The asphalt composition according to any one of claims 1 to 4, wherein the amount of the plasticizer is 0.5 to 5.0 wt % based on the total weight of the composition.

10. The asphalt composition according to claim 8, wherein the amount of the plasticizer is 0.5-5.0 wt% based on the total weight of the composition.

11. The asphalt composition according to any one of claims 1 to 4, wherein the ratio of isocyanate as the thermosetting reactive compound to the plasticizer is from 80:1 to 1:

80.

12. A method for preparing an asphalt composition according to any one of claims 1 to 11, comprising the following steps: a) heating the starting asphalt to a temperature of 110-190°C, b) adding the required amount of isocyanate and the required amount of diisononyl-1,2-cyclohexanedicarboxylate as plasticizer, wherein the order of adding the required isocyanate and plasticizer is not critical, or the isocyanate and plasticizer are mixed separately and added as a mixture, c) after step b), stirring the reaction mixture at a temperature of 110-190° C. for at least 2 hours, or homogenizing for a period of 2-180 seconds, and optionally d) determining the end of the reaction by IR spectroscopy, The reaction is carried out under an oxygen atmosphere.

13. The method according to claim 12, wherein the temperature in step a) and step c) is the same and is 110-165°C.

14. Use of the bituminous composition according to any one of claims 1 to 11 for preparing an asphalt mixture composition.

15. Use of the asphalt composition according to claim 14, wherein the granular material of the asphalt mixture composition comprises 5-100% by weight of reclaimed asphalt pavement.

16. Use according to claim 14 or 15 for pavement applications.

Citation Information

Patent Citations

  • Polymer-modified bitumen

    EP0537638B1

  • Asphalt binder compositions and methods to make and use same

    US20150191597A1

  • Asphalt composition comprising polymeric mdi

    WO2001030911A1

  • Aqueous emulsion of asphalt and emulsifiable polyisocyanate

    WO2001030912A1

  • Asphalt composition comprising polymeric MDI based prepolymer

    WO2001030913A1